CONSUMER PERCEPTIONS OF ELECTRIC AIRCRAFT: INVESTIGATING THE DRIVERS OF ACCEPTANCE AND ADOPTION - Ke, Wanchun (2025)
This study investigates and analyzes the behavioral intentions of consumers in Guangdong region towards All-Electric Aircraft (AEA) within the theoretical framework of the Theory of Planned Behavior (TPB), and uses Structural Equation Modeling (SEM) and SmartPLS to analyze the collected data. According to the existing literature, TPB and SEM have not been used to evaluate the electric aviation market in Guangdong region. The purpose of this study is exploratory, adopting a quantitative research method. Structured questionnaires are distributed to approximately 100 consumers in Guangdong to explore their overall cognition of electric aircraft, the factors influencing such cognition, and their willingness to use electric aircraft. The study finds that consumers’ attitude, subjective norm, and environmental concern have a positive impact on their adoption of the new AEA technology, while perceived behavioral control and perceived risk are found to have no effect on consumers. The results of this study provide valuable insights for airlines, aircraft manufacturers, and policymakers. By understanding consumers’ concerns and preferences, airlines can formulate more effective marketing strategies to promote electric aircraft. Aircraft manufacturers can utilize these findings to improve the design and performance of electric aircraft and address consumers’ concerns. Policymakers can formulate relevant policies to support the development and adoption of electric aircraft and promote the sustainable development of the aviation industry.